Prediction of body fat through body adiposity index and bioelectrical impedance analysis in a sample of physically active Mexican students (Predicción de grasa corporal mediante el índice de adiposidad corporal y análisis de impedancia bioeléctrica en un - Ochoa-Martinez, Paulina Yesica; Hall-López, Javier Arturo; Solano-Pineda, Ileana; Monreal Ortiz, Luis Roberto; Chacón-Araya, Yamileth; Moncada-Jiménez, José (Retos, 2018)
Abstract. Objective: To compare the body fat percentage %BF predicted through the body adiposity index (BAI) BAI in a sample of physically active Mexican college students, using bioelectrical impedance analysis (BIA) as reference method. Methods: 78 volunteered university students (20.67 ± 1.69 yrs.) partake in study considered as highly active; the %BF determined by BIA was performed using Inbody 720; BAI was calculated by anthropometric assessment from hip and height measures calculated as follows: BAI=[hip circumference (cm)/height (m)1.5]–18. Pearson’s correlation coefficient was used to evaluate the association between BAI and %BF assessed by BIA. Results: The correlations of % BF between BIA and the estimated by BAI were r = 0.81, p < 0.001 in man and r = 0.69, p < 0.001 in women. Paired t-test in man showed a significant mean difference in %BF between methods (p = 0.001). The bias of the body adiposity was 5.77± 4.2 % (CI95% = 4.40 to 7.14), indicating that the body adiposity index method measured lower %BF than the bioelectrical impedance. Paired t-test in women did not show significant difference (p = 0.355). Lin’s concordance correlation coefficient was considered poor in man (ρc = 0.49) and women (ρc = 0.63), indicating than BAI underestimating %BF in relation to the BIA. Conclusion: In physically active Mexican college students, BAI presented low agreement with %BF measured by BIA; therefore, BAI is not recommended for %BF prediction in this sample studied. Resumen. Objetivo: Comparar el porcentaje de grasa corporal % BF predicho por el índice de adiposidad corporal (BAI) y el análisis de impedancia bioeléctrica (BIA) en una muestra de estudiantes universitarios Mexicanos físicamente activos. Método: 78 estudiantes universitarios (Edad media= 20,67±1,69 años) voluntarios considerados físicamente activos mediante el cuestionario (IPAQ) participaron en el estudio; Para determinar el %GC con el método de referencia el AIB se realizó con el equipo Inbody 720; el IAC se determinó mediante valoración antropométrica de las medidas circunferencia de cadera y talla calculándose con la fórmula: IAC (%GC)=[circunferencia de cadera (cm)/talla(m)1,5]-18. Resultados: Las correlaciones de Pearson del %GC entre IAC y las estimada por AIB fue de r=0,81, p